Pengaruh kombinasi sistem tanam dan jumlah benih tanaman terhadap pertumbuhan dan hasil tanaman Padi Hitam (Oryza sativa L.) - Vera Purnama; Lusiana; Hamdan Drian Adiwijaya; Tita Kartika Dewi; Euis Maesaroh (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aimed to determine the effect of a combination of cropping systems and the number of plant seeds on the growth and yield of black rice plants. The research method used a simple randomized block design (RBD) model consisting of 6 treatment combinations with 4 replication, namely: 1) Combination of 25 x 25 tile planting system and one seed (J1B1), 2) Combination of 25 x 25 tile planting system and two seeds (J1B2), 3) Combination of 2:1 legowo cropping system and one seed (J2B1), 4) Combination of 2:1 legowo cropping system and two seeds (J2B1), 5) Combination of 4:1 legowo cropping system and one seed (J3B1), and 6) Combination legowo 4:1 cropping system and two seeds (J3B2). The results showed that the combination treatment of different cropping systems and number of seeds affected the observation of plant height at 4, 6, and 8 week after planting (WAP), as well as the number of tillers at 4, 6, and 8 WAP; number of productive tillers aged 6 and 8 WAP. Meanwhile, the combination treatment of different planting systems and the number of seeds had no effect on plant height at 2 WAP, number of tillers at 2 WAP, and HGW/plant weight. The combination of the 2:1 legowo cropping system with the number of one seed gave the best effect on observing plant height, number of productive tillers, number of panicles, and weight of 100 HGW grains. However, the combination treatment of different cropping systems and the number of seeds resulted in the same or not significantly different dry harvested grain weight (HGW) and milled dry grain weight (DGW).